Suitable flesh [videorecording (DVD)] - Paoli, Dennis; Graham, Heather, 1970-; Lewis, Judah, 2001-; Crampton, Barbara, 1962-; Davison, Bruce, 1946-; Schaech, Johnathan, 1969-; Moore, Steve, 1975-; Lovecraft, H. P. (Howard Phillips), 1890-1937 (RLJ Entertainment, 2024)
Psychiatrist Elizabeth Derby becomes obsessed with helping a young patient who's suffering from extreme personality disorder. However, it soon leads her into occult danger as she tries to escape from a horrific fate.